The Eukaryotic Microbiome: Origins and Implications for Fetal and Neonatal Life - Miller, William B. (Frontiers in Pediatrics, 2016)
All eukaryotic organisms are holobionts representing complex collaborations between the entire microbiome of each eukaryote and its innate cells. These linked constituencies form complex localized and interlocking ecologies in which the specific microbial constituents and their relative abundance differ substantially according to age and environmental exposures. Rapid advances in microbiology and genetic research techniques have uncovered a significant previous underestimate of the extent of that microbial contribution and its metabolic and developmental impact on holobionts. Therefore, a re-calibration of the neonatal period is suggested as a transitional phase in development that includes the acquisition of consequential collaborative microbial life from extensive environmental influences. These co-dependent, symbiotic relationships formed in the fetal and neonatal stages extend into adulthood and even across generations.